Going Serverless. - Savage, Neil (Communications of the ACM, 2018)
The article discusses the use of serverless computing by businesses and application developers in order to no longer need to deal with the expense of buying or maintaining servers while being able to focus on the program they need to run without worrying about the machine it is on or the resources it requires.